2021
DOI: 10.52547/iem.7.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Study of Antibacterial Activity of Gentamicin-Cetirizine on Uropathogenic Escherichia coli Isolates

Abstract: Background: Urinary tract infections (UTIs) cause a wide range of infections in individuals; they are common nosocomial infections that have recently become difficult to treat because of the increased emergence of multidrug-resistant bacteria. The present study aimed to determine and compare the minimum inhibitory concentration of gentamicin alone and in combination with cetirizine against Escherichia coli strains isolated from hospitalized patients with UTI.Materials & Methods: This study was performed on 76 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Antibiotic resistance in bacteria can develop through various mechanisms, including the acquisition of drug-resistant genes through chromosomal alterations, plasmid transfer, or genetic mutations. This phenomenon has given rise to the emergence of multidrug-resistant (MDR), extensively drug-resistant (XDR), and pandrug-resistant (PDR) clinical strains, particularly prevalent in low-and middle-income countries [6]. Strains of E. coli are classified as MDR when they exhibit non-susceptibility to one or more antibiotics belonging to a minimum of three distinct antibiotic classes.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic resistance in bacteria can develop through various mechanisms, including the acquisition of drug-resistant genes through chromosomal alterations, plasmid transfer, or genetic mutations. This phenomenon has given rise to the emergence of multidrug-resistant (MDR), extensively drug-resistant (XDR), and pandrug-resistant (PDR) clinical strains, particularly prevalent in low-and middle-income countries [6]. Strains of E. coli are classified as MDR when they exhibit non-susceptibility to one or more antibiotics belonging to a minimum of three distinct antibiotic classes.…”
Section: Introductionmentioning
confidence: 99%
“…Most UTIs are usually harmless and not serious; however, misdiagnosis or delay in treatment could lead to serious complications, such as urinary tract disorders, hypertension, uremia, preterm delivery, or even miscarriage in pregnant women. Studies in different communities have shown that Gram-negative bacilli are the most common etiological causes of UTIs, among which Escherichia coli accounts for more than 80% of UTIs [1,2] . Proper treatment of UTIs is based on the selection of a suitable and highly effective antibiotic.…”
Section: Introductionmentioning
confidence: 99%